Light quantity, not photoperiod terminates diapause in the crustacean Daphnia. (14th September 2018) - Ślusarczyk, M.; Flis, S.
Abstract: While light controls dormancy occurrence in various groups of organisms, it may play different roles in its initiation and termination. Seasonally changing photoperiod is frequently used to announce cyclical events and trigger diapause initiation in advance of seasonal changes. A similar role for photoperiod has often been uncritically extended to diapause termination. In the present study we investigated the role of photoperiod and light quantity in diapause termination of resting eggs of a freshwater crustacean. In a few tests, a cohort of resting eggs of Daphnia magna were incubated under various light conditions. A short‐day photoperiod appeared as successful as a long day or artificial one in reactivating resting eggs. The hatching proportion was more related to total light energy applied than to its temporal pattern. The hatching proportion increased asymptotically from 0% reported after 6 h of light exposition or shorter, to 32% after 48 h of total light period of moderate intensity (55 μmol m −2 s −1 ). Longer light exposition did not increase hatching success considerably. A 15 times lower light intensity (3.5 vs. 55 μmol m −2 s −1 ) applied for a given period of time (96 h) resulted in a 3 times lower hatching success. Our results challenge the common opinion of the decisive role of photoperiod in diapause termination and support the alternative light‐energy threshold hypothesis. It seems that the resting eggs of D. magna do not monitor seasonal changes of the photoperiod but reactivate after completion of the refractory period and accumulation of a certain amount of light energy dose.